Mapping Quantitative Trait Loci for High-Temperature Adult-Plant Resistance to Stripe Rust in Spring Wheat PI 197734 Using a Doubled Haploid Population and Genotyping by Multiplexed Sequencing - Liu, Lu; Yuan, Congying; Wang, Meinan; See, Deven R.; Chen, Xianming (Frontiers in Plant Science, 2020)
Stripe rust caused by Puccinia striiformis f. sp. tritici (Pst) is a global concern for wheat production. Spring wheat cultivar PI 197734, of Sweden origin, has shown high-temperature adult-plant resistance to stripe rust for many years. To map resistance quantitative trait loci (QTL), 178 doubled haploid lines were developed from a cross of PI 197734 with susceptible AvS. The DH lines and parents were tested in fields in 2017 and 2018 under natural infection of Pst and genotyped with genotyping by multiplexed sequencing (GMS). Kompetitive allele specific PCR (KASP) and simple sequence repeat (SSR) markers from specific chromosomal regions were also used to genotype the population to validate and saturate resistance QTL regions. Two major QTL on chromosomes 1AL and 3BL and one minor QTL on 2AL were identified. The two major QTL, QYrPI197734.wgp-1A and QYrPI197734.wgp-3B, were detected in all tested environments explaining up to 20.7% and 46.8% phenotypic variation, respectively. An awnletted gene mapped to the expected distal end of chromosome 5AL indicated the accuracy of linkage mapping. The KASP markers converted from the GMS-SNPs in the 1A and 3B QTL regions were used to genotype 95 US spring wheat cultivars and breeding lines, and they individually showed different percentages of polymorphisms. The haplotypes of the three markers for the 1A QTL and four markers for the 3B QTL identified 37.9% and 21.1% of the wheat cultivar/breeding lines possibly carrying these two QTL, indicating their usefulness in marker-assisted selection for incorporating the two major QTL into new wheat cultivars.